A Current Review and Global Benchmark on the Challenges and Prospect of Air Pollution Mitigation in Malaysia - Goh, Jie Heng; Lim, En Qi; Tai, Li Jia; Ong, Chun Keat; Khor, Wei Han (Progress in Energy and Environment, 2025)
The paper delves into the global air pollution issue, with a particular focus on Malaysia as a member of the ASEAN community. It underscores that air pollution is not merely a statistical concern but a daily reality impacting public health and the environment. Over time, there has been a significant increase in mortality and hospitalization rates attributed to air pollution. Human activities, including industry, transportation, and waste management, are identified as major contributors to air pollution. The paper discusses Malaysia's governmental efforts to address air pollution, encompassing air quality monitoring and control systems, environmental protection acts, promotion of alternative green energy sources, and carbon emission control measures. Despite the potential of renewable energy sources such as wind and hydropower, their limitations in fully replacing traditional energy sources are highlighted. Furthermore, the paper identifies methods to control urban air pollution by reviewing successful strategies implemented in other developed countries, such as advanced public transport systems and vehicle registration and age limitations. In conclusion, this paper provides valuable insights into the air pollution issue in Malaysia and offers suggestions for controlling and mitigating its impact, thus, contributing towards cleaner air and healthier environments.